2016
DOI: 10.2147/ott.s115974
|View full text |Cite
|
Sign up to set email alerts
|

Positive expression of KIF20A indicates poor prognosis of glioma patients

Abstract: Glioma patients have a poor overall survival; however, patients can show distinct clinical outcomes due to the high heterogeneity of the tumor, which may be indicated by certain clinicobiological parameters. Kinesin family member 20A (KIF20A), which participates in cytokinesis and intracellular transportation, has been recently reported to be upregulated in pancreatic cancer, breast cancer, and bladder cancer. In the current study, we investigated the expression of KIF20A in gliomas and its significance in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…In addition, univariate as well as multivariate Cox regression analyses demonstrated that KIF20A expression can be considered as an independent prognostic factor of OS in patients with LUAD. Our findings were highly consistent with previous studies about the prognostic impact of KIF20A in other cancers …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, univariate as well as multivariate Cox regression analyses demonstrated that KIF20A expression can be considered as an independent prognostic factor of OS in patients with LUAD. Our findings were highly consistent with previous studies about the prognostic impact of KIF20A in other cancers …”
Section: Discussionsupporting
confidence: 93%
“…Using chi‐square test, we analyzed the correlation between KIF20A expression and Ki‐67 in LUAD tissues. Our result showed that KIF20A expression in LUAD was highly positively correlated with Ki‐67 level, bearing similarities with observations from Duan et al who reported that the expression of KIF20A was relevant to Ki67 expression in gliomas. The Pearson's correlation analysis of the two factors in LUAD tissues from TCGA dataset was consistent with our findings, implying that KIF20A could be an indicator of tumor proliferation as well as Ki‐67.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover CDC20, described as prognostic in colon64 and breast65, has been identified as relevant in KICH and LUAD in our study. Finally NCAPG and KIF20A genes of prognostic value in gliomas6667 were found relevant here in LUAD. We also identified a few novel associations in lung tumours (LUAD), for instance CENPK has not previously been associated with this cancer type, even though the gene had already been associated to ovarian cancer68.…”
Section: Discussionmentioning
confidence: 64%